The Role of Arbitrators in Settling the Jabodebek LRT Project Construction Dispute - Khairun Nizam, M. Ardhan Hakim Lubis, Muhammad Furqan Alrizky, Wahyu Hidayat, Alfarobi (Jurnal Sahabat ISNU SU, 2024)
Large-scale infrastructure projects, such as the Jabodebek Light Rail Transit (LRT) development, involve complex contractual relationships that increase the likelihood of disputes among project stakeholders. Delays, contract modifications, technical issues, and financial disagreements frequently arise during project implementation, making efficient dispute resolution essential to ensure project continuity. Arbitration has emerged as a preferred alternative dispute resolution (ADR) mechanism due to its efficiency, confidentiality, and finality. This study aims to examine the role of arbitrators in resolving construction disputes arising from the Jabodebek LRT project and to analyze the advantages and limitations of arbitration in infrastructure development disputes. The research employed a qualitative approach using descriptive analysis. Data were collected through library research by reviewing legislation, legal literature, journal articles, and relevant case studies concerning construction arbitration in Indonesia. The findings indicate that arbitrators play a significant role in providing fair, efficient, and legally binding dispute resolution while maintaining the confidentiality of the parties involved. Arbitration also enables disputing parties to appoint arbitrators with specialized expertise in construction law and engineering, resulting in more informed and practical decisions. However, arbitration presents several challenges, including relatively high costs, the absence of an appeal mechanism due to the final and binding nature of arbitral awards, and the dependence of dispute resolution quality on the competence and integrity of arbitrators. The study concludes that arbitration remains an effective mechanism for resolving construction disputes in large-scale infrastructure projects, provided that competent arbitrators are appointed and the arbitration process is conducted in accordance with applicable legal principles to ensure legal certainty, fairness, and project sustainability.